Game Change in Colorado: Widespread Use Of Long‐Acting Reversible Contraceptives and Rapid Decline in Births Among Young, Low‐Income Women. Issue 3 (24th June 2014) - Ricketts, Sue; Klingler, Greta; Schwalberg, Renee
Abstract : Context: Long‐acting reversible contraceptive (LARC) methods are recommended for young women, but access is limited by cost and lack of knowledge among providers and consumers. The Colorado Family Planning Initiative (CFPI) sought to address these barriers by training providers, financing LARC method provision at Title X–funded clinics and increasing patient caseload. Methods: Beginning in 2009, 28 Title X–funded agencies in Colorado received private funding to support CFPI. Caseloads and clients' LARC use were assessed over the following two years. Fertility rates among low‐income women aged 15–24 were compared with expected trends. Abortion rates and births among high‐risk women were tracked, and the numbers of infants receiving services through the Special Supplemental Nutrition Program for Women, Infants and Children (WIC) were examined. Results: By 2011, caseloads had increased by 23%, and LARC use among 15–24‐year‐olds had grown from 5% to 19%. Cumulatively, one in 15 young, low‐income women had received a LARC method, up from one in 170 in 2008. Compared with expected fertility rates in 2011, observed rates were 29% lower among low‐income 15–19‐year‐olds and 14% lower among similar 20–24‐year‐olds. In CFPI counties, the proportion of births that were high‐risk declined by 24% between 2009 and 2011; abortion rates fell 34% and 18%, respectively, among women aged 15–19 and 20–24. Statewide, infant enrollment in WIC declined 23% between 2010 and 2013. Conclusions: Programs that increase LARC use among young, low‐income women may contribute to declines in fertility rates, abortion rates and births among high‐risk women.